Lipidized analogues of the anorexigenic CART (cocaine- and amphetamine-regulated transcript) neuropeptide show anorexigenic and neuroprotective potential in mouse model of monosodium-glutamate induced obesity - Charvát, Vilém; Strnadová, Anna; Myšková, Aneta; Sýkora, David; Blechová, Miroslava; Železná, Blanka; Kuneš, Jaroslav; Maletínská, Lenka; Pačesová, Andrea (European journal of pharmacology, 2024)
AIMS: This study investigates the neuroprotective effects of lipidized analogues of 2-SS-CART(61-102) derived from anorexigenic neuropeptide cocaine- and amphetamine-regulated transcript peptide (CARTp) in light of the link between obesity, its comorbidities, and the development of Alzheimer's disease. METHODS: We introduce novel lipidized analogues derived from 2-SS-CART(61-102), a specific analogue of natural CART(61-102), with two disulfide bridges. Using hypothermic PC12 cells, we tested the effect of the most potent analogues on Tau phosphorylation. We further described the anorexigenic and neuroprotective potential of subcutaneously (SC) injected lipidized CARTp analogue in a mouse model with prediabetes and obesity induced by neonatal monosodium glutamate (MSG) administration. RESULTS: Compared to the non-lipidized 2-SS-CART(61-102), all lipidized analogues exhibited a potent binding affinity to PC12 cells and enhanced in vitro stability in rat plasma. Two most potent lipidized analogues attenuated hypothermia-induced Tau hyperphosphorylation at multiple epitopes. Subsequently, chronic SC treatment with palm-2-SS-CART(61-102) significantly decreased body weight and food intake, improved metabolic parameters, decreased level of pTau and increased neurogenesis in hippocampi of obese MSG mice. CONCLUSION: Our unique CARTp analogue palm-2-SS-CART(61-102) shows promise as a potent anti-obesity and neuroprotective agent.
Keywords: PC12 Cells; Animals; Sodium Glutamate; tau Proteins; lipidy; Obesity; anorektika; Mice; Lipids; myši; proteiny nervové tkáně; Appetite Depressants; Nerve Tissue Proteins; obezita; fosforylace; modely nemocí na zvířatech; Male; Neuroprotective Agents; buňky PC12; Disease Models, Animal; glutamát sodný; krysa rodu Rattus; proteiny tau; mužské pohlaví; zvířata; Mice, Inbred C57BL; Rats; Phosphorylation; myši inbrední C57BL; neuroprotektivní látky